PENGARUH SARANA PENDUKUNG SISTEM INFORMASI AKUNTANSI, SISTEM PENGENDALIAN INTERN PEMERINTAH DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PENGELOLA KEUANGAN PADA SEKRETARIAT DAERAH KABUPATEN KEPULAUAN SANGIHE - Makatengkeng, Gracelia; Kalangi, Lintje; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to examine the effect of Supporting tools of Accounting Information Systems, Government Internal Control Systems And Organizational Culture On Employees Performance at Sekretariat Daerah Kabupaten Kepulauan Sangihe. This research is a quantitative study, using primary data through a questionnaire. Respondents in this study were 50 employees. The analytical method used in this research is multiple linear regression with the help of the SPSS version 28 program. The results showed that the variables of the government's internal control system and organizational culture are capable to help improve employee performance, while the results of research on the variables of supporting accounting information systems showed that these variables are not capable to help improve employee performance at Sekretariat Daerah Kabupaten Kepulauan Sangihe.